The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1128/jvi.05053-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glycosylation Profiles of HIV-1 Transmitted/Founder Envelopes by Mass Spectrometry

Abstract: The analysis of HIV-1 envelope carbohydrates is critical to understanding their roles in HIV-1 transmission as well as in binding of envelope to HIV-1 antibodies. However, direct analysis of protein glycosylation by glycopeptide-based mass mapping approaches involves structural simplification of proteins with the use of a protease followed by an isolation and/or enrichment step before mass analysis. The successful completion of glycosylation analysis is still a major analytical challenge due to the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 69 publications
5
151
0
Order By: Relevance
“…Consistent with the notion that uninterpretable glycan density results from sample heterogeneity rather than from refinement problems, we found unambiguous density at positions that should be homogenous, e.g. at N332 gp120 , a high-mannose-only site (Behrens et al, 2016), whereas sites predicted to be more heterogeneous, such as N156 gp120 (Behrens et al, 2016;Go et al, 2011), exhibited some uninterpretable heterogeneous electron density. Although the relatively low resolution of our crystal structures and heterogeneous glycosylation compounded inherent difficulties in making unambiguous glycan assignments, we built coordinates into very extensive densities (e.g.…”
Section: Glycan Interpretation and Refinementsupporting
confidence: 70%
See 2 more Smart Citations
“…Consistent with the notion that uninterpretable glycan density results from sample heterogeneity rather than from refinement problems, we found unambiguous density at positions that should be homogenous, e.g. at N332 gp120 , a high-mannose-only site (Behrens et al, 2016), whereas sites predicted to be more heterogeneous, such as N156 gp120 (Behrens et al, 2016;Go et al, 2011), exhibited some uninterpretable heterogeneous electron density. Although the relatively low resolution of our crystal structures and heterogeneous glycosylation compounded inherent difficulties in making unambiguous glycan assignments, we built coordinates into very extensive densities (e.g.…”
Section: Glycan Interpretation and Refinementsupporting
confidence: 70%
“…In other cases, the interpretation of our electrondensity maps was partially based on supporting experimental data: e.g. for the N301 gp120 glycan a core fucose was not ordered in our maps, but the N301 gp120 glycan was modeled as complextype in our structures based on mass-spectrometric data (Go et al, 2011). As expected given the large degree of glycan heterogeneity in HIV-1 Env (Doores, 2015), the glycan density was sometimes ambiguous.…”
Section: Glycan Interpretation and Refinementmentioning
confidence: 96%
See 1 more Smart Citation
“…We and others have reported that founder viruses generally have fewer glycosylation sites and more compact Envs (9,(31)(32)(33), and our earlier studies also demonstrated that newly transmitted viruses were not escape variants from PL-neutralizing antibodies in the donor (9). Recent studies have suggested that subtype A and C founder viruses bind efficiently to the gut homing receptor α4β7 expressed on a subset of highly susceptible CD4 T lymphocytes and that this property can be reduced with evolution of the virus after transmission (34).…”
Section: Discussionmentioning
confidence: 99%
“…Pal et al showed that gp41 from viruses prepared in MOLT-3 cells was Endo H resistant, but when prepared in the presence of an ER mannosidase inhibitor, 1-deoxymannojirimycin, gp41 became sensitive to Endo H digestion (59). More recent work by us and by Go and colleagues has shown that the gp41 glycans on recombinant gp140 trimers (13,60,61), including the SOSIP trimer (14), are predominantly complex type and that these structures are generally more dependent on producer cells. In this study, we were able to record the chromatograms of labeled glycans from PGT151-isolated pseudovirion-derived material and cell surface-associated Env to provide a more detailed description of glycan structures present on native virion-derived gp41.…”
Section: Oligomannose Isomers Are the Same On Pbmc-derived Env And Rementioning
confidence: 99%